CLINICAL CHARACTERISTICS AND TREATMENT OUTCOMES OF POSTPARTUM HEMORRHAGE DUE TO UTERINE ATONY USING FOLEY CATHETER BALLOON TAMPONADE AT HAI PHONG OBSTETRICS AND GYNECOLOGY HOSPITAL, 2020-2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe clinical characteristics of postpartum hemorrhage patients with uterine atony after vaginal delivery treated by Foley balloon tamponade and evaluate treatment outcomes and associated factors.Subjects and methods: Cross-sectional descriptive study on 50 patients with postpartum hemorrhage with uterine atony after vaginal delivery, treated by Foley catheter 30F balloon tamponade at Hai Phong Obstetrics and Gynecology Hospital, from 1/9/2020 to 1/9/2025.Results: Mean age 28.6 ± 6.1 years; 100% vaginal delivery. Prolonged labor was the most common risk factor (32%). Mean blood loss 986 ± 342 ml; 72% presented with hemorrhagic shock. Complete balloon tamponade success rate was 88% (95% CI: 75.7-95.5%). Overall uterine preservation rate was 92% (95% CI: 80.8-97.8%). Hysterectomy rate 8%. No maternal deaths, no postpartum infection. Factors associated with failure: blood loss ≥ 1500 ml (p = 0.001), time to balloon insertion ≥ 30 minutes (p = 0.002), hemoglobin < 8 g/dL (OR = 10.7; p = 0.030), adequate inflation < 80 ml (p = 0.04).Conclusion: Foley 30F balloon tamponade achieved 92% uterine preservation rate, safe with no infectious complications when combined with broad-spectrum antibiotic prophylaxis. Early intervention within 30 minutes and adequate inflation ≥ 80 ml are critical technical determinants of success.
Keywords: Postpartum hemorrhage, uterine atony, uterine balloon tamponade, Foley catheter, vaginal delivery.